PENGARUH PENALARAN MORAL, RETALIASI, RELIGIUSITAS, DAN GENDER TERHADAP NIAT MAHASISWA MELAKUKAN TINDAKAN WHISTLEBLOWING (Studi Empiris Pada Mahasiswa Akuntansi Universitas Sarjanawiyata Tamansiswa) - Sri Ayem; Rumdoni (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2021)
This study aims to examine the effect of moral reasoning, retaliation, religiosity, and gender on student’s intention to take whistleblowing. This reseach method uses quantitative descriptive methods and primary data in the form of a questionnaire distributed via google form. The sample in this study were accounting students at the Sarjanawiyata Tamansiswa University of 2017 and 2018, with a total of 84 respondents. The sampling technique used snowball sampling. The data analysis method uses multiple linear regression hypothesis test which is processed using the IBM SPSS version 20 program. The result of this study indicated that moral reasoning, retaliation, and gender have no effect on the intention of students to take whistleblowing, while religiosity has a positive effect on students intenstion on take whistleblowing.)